Spacecraft attitude dynamics - Hughes, Peter C. 1940- (Dover Publications, 2004)
From its roots in classical mechanics and reliance on stability theory to the evolution of practical stabilization ideas, this volume covers environmental torques encountered in space; energy dissipation; motion equations for four archetypical systems; orientation parameters; illustrations of key concepts with on-orbit flight data; and typical engineering hardware. 1986 edition.
Keywords: Space vehicles -- Attitude control systems.; Space vehicles -- Dynamics.; Astrodynamics.; elektronické knihy; electronic books